2005
DOI: 10.1097/01.aud.0000188201.86799.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Streamlined Programming Procedures for the Nucleus Cochlear Implant with the Contour Electrode Array

Abstract: Two streamlined programming procedures are recommended for use in the clinical setting: (1) interpolating across three measured T-levels and three measured C-levels and (2) interpolating across five measured T- or C-levels and using the interpolated profile for fitting of the alternative profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 7 publications
0
30
2
1
Order By: Relevance
“…Significant progress has been made in efficient fitting of cochlear implants, includes measuring only the comfortable loudness level (Clarion), streamlining the mapping by interpolating the T and C levels in a subset of the electrodes [168], and optimizing the map by genetic algorithms [169]. Because structured training has been shown to benefit cochlear implant performance [170], a future fitting system may be integrated with a structured training system.…”
Section: Fitting Programmentioning
confidence: 99%
“…Significant progress has been made in efficient fitting of cochlear implants, includes measuring only the comfortable loudness level (Clarion), streamlining the mapping by interpolating the T and C levels in a subset of the electrodes [168], and optimizing the map by genetic algorithms [169]. Because structured training has been shown to benefit cochlear implant performance [170], a future fitting system may be integrated with a structured training system.…”
Section: Fitting Programmentioning
confidence: 99%
“…If any of these electrodes were deactivated in programming, the adjacent electrode was used. The interpolation of the electrodes is used in clinical practice and establishes the minimum and maximum levels from a sample of electrodes (19) . The other parameters of the programming that compose the map, such as speech coding strategy, speed, and number of maxima, were not modified during the RP and live programming (LP).…”
Section: Methodsmentioning
confidence: 99%
“…Plant et al 77 showed that 2 streamlined techniques could be successfully used in the clinical setting. The first technique was interpolation across 3 measured threshold levels and 3 measured comfortable listening levels, while the other was interpolation across 5 measured threshold or comfortable levels and the interpolated profile was used for fitting the alternative profile.…”
Section: Streamlined and Self-programmingmentioning
confidence: 99%
“…77 They can also significantly reduce clinical fitting time. 78 Custom Sound is designed on streamlined fitting principles, providing an efficient and effective method to fit cochlear implant recipients, especially during initial activation.…”
Section: Custom Sound Suite™mentioning
confidence: 99%